Is there any benefit in associating neuraxial anesthesia to general anesthesia for coronary artery bypass graft surgery? - Barbosa,Fabiano Timbó (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: The use of neuraxial anesthesia in cardiac surgery is recent, but the hemodynamic effects of local anesthetics and anticoagulation can result in risk to patients. OBJECTIVE: To review the benefits of neuraxial anesthesia in cardiac surgery for CABG through a systematic review of systematic reviews. CONTENT: The search was performed in Pubmed (January 1966 to December 2012), Embase (1974 to December 2012), The Cochrane Library (volume 10, 2012) and Lilacs (1982 to December 2012) databases, in search of articles of systematic reviews. The following variables: mortality, myocardial infarction, stroke, in-hospital length of stay, arrhythmias and epidural hematoma were analyzed. CONCLUSIONS: The use of neuraxial anesthesia in cardiac surgery remains controversial. The greatest benefit found by this review was the possibility of reducing postoperative arrhythmias, but this result was contradictory among the identified findings. The results of findings regarding mortality, myocardial infarction, stroke and in-hospital length of stay did not show greater efficacy of neuraxial anesthesia.